SOSIALISASI ETIKA PENGGUNAAN HANDPHONE BAGI SISWA SMP DI KOTA BENGKULU - Heri Supriyanto; Susri Adeni; Dedi Supriyadi (DHARMA RAFLESIA, 2017)
The use of communication media, especially mobile phones is unfortunately not felt right. It sees a lot of users who do not 'unethical' when using mobile phones; for example manychildren of school age or adolescent even adults use phone while driving a motorcycle or acar. Another case is the misused of mobile phones such as pornographic video recordingmade by one of the school students in the city of Bengkulu. The video then uploaded to theinternet media like youtube.com. It looks like the users of communication media is not orshould not even understand how to communicate well using the media. The rise of the'sights' of this makes the basis for the holding of this service activity. The activity goal is toprovide knowledge to students with regard to communication media, helping students todevelop a critical understanding and adequate information about the use of goodcommunication media, providing knowledge to students on how good ethics in the use ofcommunication media, especially mobile phones and equip students early capable ofcommunicating with both to make use of existing media, especially mobile phones. Thetarget audience of the communication media education activities is students of SMP 1 andSMP 11, and SMP 7 representing students in the city of Bengkulu with the number ofattending students in this event each grade level were 10 people representing his friends.The activities are lectures, discussion, and simulation of media education with the ultimategoal of improved understanding of the students in the use communication media, especiallymobile phones. The result shows that many of students have new knowledge about theethics of phone using.Keywords: communication, phone, communication ethics, mass media